(untitled) (Ameghiniana, 2020)
“Larger” foraminifera appear in different lineages through the evolutionary history of the group. Traditionally, the reason why benthic forams of calcareous wall—mainly milliolids and rotallids—reached centimetric dimensions was attributed to the endosymbiotic relationships with algae. The ecological requirements and morphological characteristics of tests are known from experimental studies in extant forms. These requirements and characteristics are fundamental to establish and maintain symbiosis with diverse chlorophytes, rhodophytes, diatoms, dinoflagellates and cyanobacteria groups. Such relationships are neither exclusive or a sine qua non condition for larger taxa. This work aims to explore the published literature regarding this topic in order to sort out how experimental and palaeontological evidences can be of use to infer symbiotic relationships on the fossil record.